Integrating augmented reality into engineering education: Development and evaluation of tensile testing learning media - Uum Sumirat; Juliana Juliana; Lazuardi Imani Hakam; Usep Suhud; Inomjon Qudratov (Jurnal Cakrawala Pendidikan, 2026)
The integration of Augmented Reality (AR) into technical and vocational education has gained considerable attention as a means of bridging the gap between abstract theoretical content and applied industrial competencies. However, empirical evidence regarding its effectiveness in mechanics of materials instruction, particularly within the context of manufacturing engineering training, remains limited. This study aimed to design, develop, and evaluate an AR-based instructional medium for tensile testing procedures, targeting competency development among engineering students. The development process followed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design model, incorporating competency-based and mastery learning frameworks. A pre-experimental one-group pretest-posttest design was employed with 36 engineering students drawn from three higher education institutions in Indonesia. Media feasibility was assessed through expert validation, yielding scores of 79% for media quality and 91% for content accuracy, both indicating suitability for instructional use. Learning outcomes were measured using normalized gain (N-Gain) analysis, with results indicating a mean N-Gain score of 0.47, classified as moderate improvement according to Hake's (1998) criteria. These findings suggest that AR-based instructional media may serve as an effective tool for supporting technical training in mechanics of materials, particularly for facilitating three-dimensional visualization of complex physical phenomena such as tensile deformation and stress-strain behavior. Nevertheless, the moderate gain score indicates that further development, notably the incorporation of audio elements and higher-order synthesis tasks, may be required to fully support advanced competency levels. The study contributes empirical evidence to the growing body of literature on immersive technology integration in engineering education within Industry 4.0 contexts.